2007
DOI: 10.14742/ajet.1256
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers' attitudes about the use of learning management systems in engineering education: A Swedish case study

Abstract: <span>The purpose of this study was to examine lecturers' attitudes towards learning management systems (LMS), with particular reference to identifying obstacles to increased use. At the University College of Borås, Sweden, 22 lecturers who had used </span><em>WebCT</em><span> during the previous 9 months were interviewed. The answers show that most of the lecturers, including those who only used minor parts of the LMS, believed that they could benefit from using a LMS in the futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
1
13
0
2
Order By: Relevance
“…The attitude of faculty members within institutions towards LMS use for teaching endeavours is hypothesised to be context specific, depending on the type of LMS and the sociocultural factors of the country, the institutions, and personal experiences of the faculty members. For example, in Sweden, a study indicated that the 'perceived ease-of-use hypothesis' developed by Rogers (2003) was not supported, but that for faculty members, cost and benefit were more important (Garrote & Pettersson, 2007). Other studies in Saudi Arabia have rejected the hypothesis that LMS adoption was based on the complexities of the LMS system and faculty members believing that it provided no pedagogical benefit (Coates, James, & Baldwin, 2005;Govindasamy, 2001;Dooley, 1999;Davis, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The attitude of faculty members within institutions towards LMS use for teaching endeavours is hypothesised to be context specific, depending on the type of LMS and the sociocultural factors of the country, the institutions, and personal experiences of the faculty members. For example, in Sweden, a study indicated that the 'perceived ease-of-use hypothesis' developed by Rogers (2003) was not supported, but that for faculty members, cost and benefit were more important (Garrote & Pettersson, 2007). Other studies in Saudi Arabia have rejected the hypothesis that LMS adoption was based on the complexities of the LMS system and faculty members believing that it provided no pedagogical benefit (Coates, James, & Baldwin, 2005;Govindasamy, 2001;Dooley, 1999;Davis, 1989).…”
mentioning
confidence: 99%
“…in their specific university, within a specific country. This is essential because a 'one-size-fits-all' approach to researching LMS adoption and usage may not be appropriate (Garrote & Pettersson, 2007). On this note, this study looks into the faculty members' attitude towards LMS usages by establishing the relationship between various LMS variables and personal experiences for academic purposes with context in mind.…”
mentioning
confidence: 99%
“…The study sample comprises faculty at King Abdulaziz University (KAU) in Saudi Arabia. Previous studies show the importance of LMS training offered by institutions (Bradley & Lee, 2007;Dorobăt & Năstase, 2010;Garrote & Pettersson, 2007;Lonn & Teasley, 2009) and the significant effects of such training on both PU and PEU (Agarwal & Prasad, 1999;Igbaria et al, 1995). However, none of these studies specifies the timing of the training, whereas in the present study, we consider only LMS training conducted immediately prior to implementation.…”
Section: Introductionmentioning
confidence: 94%
“…According to Garrote and Pettersson (2007), educational institutions should provide training to their instructors in regard to understanding and using an LMS until it becomes a routine part of their faculty's teaching. The researchers also noted that LMS training makes it easier for instructors to work with an LMS with less effort.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Um SGA é uma ferramenta TIC adequada para a comunicação de estudantes, docentes e outros participantes, sendo útil também para distribuir material das disciplinas e trabalhar documentos conjuntamente, além de possibilitar a realização de avaliações digitais, entre outras funções (BRITAIN;LIBER, 1999;DUTTON;CHEONG;PARK, 2004;SEEGER;ÅSTRÖM, 2005;PETTERSSON, 2007;GARRO-TE JURADO, 2012). Atualmente, existe uma grande oferta de programas com essa proposta, tanto os comercializáveis (WebCT, por exemplo) como os de código aberto (Moodle).…”
Section: Sistemas De Gestão De Aprendizagem -Sga E Recursos Educacionunclassified